The Effects of NMDA Receptor Blockade on Sensory-Evoked Responses in Superficial Layers of the Rat Barrel Cortex - Lebedeva, Julia; Zakharov, Andrey; Burkhanova, Gulshat; Chernova, Kseniya; Khazipov, Roustem (Frontiers in Cellular Neuroscience, 2019)
Transmission of excitation from L4 to L2/3 is a part of the canonical circuit of cortical sensory signal processing. While synapses from L4 to L2/3 are mediated by both AMPA and NMDA glutamate receptors, previous studies have suggested that sensory-evoked excitation of neurons in the supragranular layers is almost entirely mediated by NMDA receptors. Here, we readdressed this question using extracellular recordings of sensory-evoked potentials (SEPs) and multiple unit activity (MUA) in the rat barrel cortex. We found that blockade of NMDA receptors using the selective antagonist dAPV profoundly inhibited the late part of L2/3 SEP and MUA response but did not affect its initial part. Our results indicate that both non-NMDA and NMDA receptors are involved in the sensory signal transmission from L4 to L2/3. While non-NMDA receptors mediate fast transmission of sensory signals, NMDA receptors are involved in the generation of the late phase of the sensory-evoked response in supragranular layers.